Science and art in Peruvian prehistory - Escomel, Edmundo (1920)
Art and cultivated so cleverly .Developed between pre-Spanish conquest Peru has not only beauty reasons understood if also scientific issues that have caused controversies that persist for some, while others believe they have already found the solution embodying the unknowns.